Pharmacokinetics and tissue penetration of tazobactam administered alone and with piperacillin. - Wise, R (1991)
The pharmacokinetics of tazobactam (500 mg) administered intravenously alone were compared with the pharmacokinetics of tazobactam coadministered with piperacillin (4 g), and the penetration into an inflammatory exudate in six healthy males was studied. Piperacillin influenced the pharmacokinetics of tazobactam. The mean levels of tazobactam in plasma at 4 h were 0.6 microgram/ml when it was given alone and 1.2 micrograms/ml when it was given with piperacillin (P = 0.0003). The mean total clearances of tazobactam were 203.5 and 134.2 ml/min (P = 0.035) when it was given alone and with piperacillin, respectively There were no significant differences in the elimination half lives, areas under the concentration-time curve from 0 h to infinity, or volumes of distribution. Inflammatory exudate penetration was rapid, and the mean maximum levels of tazobactam attained were 6.4 and 11.3 micrograms/ml when it was given alone or with piperacillin, respectively (P less than 0.06). The mean percent penetration of tazobactam and the area under the concentration-time curve from 0 h to infinity in inflammatory exudate were greater when tazobactam was given with piperacillin. The mean 24-h urinary recoveries of tazobactam were 63.7% +/- 7.9% when it was given alone and 56.8% +/- 2.7% when it was given with piperacillin. The explanation for the differences in the pharmacokinetics of tazobactam when it was administered alone compared with those when it was given with piperacillin was unclear.